Meta-analysis of the diagnostic value of exosomal microRNAs in renal cell carcinoma - Li, Qingru; Tian, Jing; Chen, Cuiqing (Frontiers in Oncology, 2024)
AimThis meta-analysis aims to evaluate the potential of exosomal microRNAs(Exo-miRs) as diagnostic biomarkers for renal cell carcinoma(RCC).MethodsClinical studies reporting the use of Exo-miRs in the diagnosis of RCC were retrieved from PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang, VIP, and Chinese Biomedical Literature Database (SinoMed). After relevant data were screened and extracted, the quality of the included studies was assessed using the QUADAS-2 tool. The Meta-disc (version 1.4) software was used to analyze the heterogeneity of threshold/non-threshold effects in the included studies. The Stata MP (version 16.0) software was used to calculate sensitivity(Sen), specificity(Spe), positive likelihood ratio(+LR), negative likelihood ratio(-LR), area under the curve(AUC), diagnostic odds ratio(DOR), and publication bias.ResultsA total of 11 studies were included in this meta-analysis. Spearman correlation coefficient was 0.319 (P = 0.075; >0.05), indicating no threshold effects. The pooled Sen, Spe, +LR, -LR, DOR, and AUC were 0.73 (95% CI, 0.68–0.78), 0.81 (95% CI, 0.76–0.85), 3.80 (95% CI, 3.02–4.77), 0.33 (95% CI, 0.28–0.40), 11.48 (95% CI, 8.27–15.95), and 0.84 (95% CI, 0.80–0.87), respectively. No publication bias was detected among the included studies.ConclusionThe expression of Exo-miRs plays an important role in the diagnosis of RCC. However, owing to the limited number of included studies and heterogeneity among them, further clinical research is necessary to verify the findings of this meta-analysis.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42023445956.